Administration of a recombinant ALDH7A1 (rA7) indicates potential regulation of the metabolite and immunology pathways in Atlantic salmon infected with Aeromonas salmonicida. Issue 7 (1st March 2021) - Li, Xiaohao; Fan, Kunpeng; Liu, Yafang; Liu, Ying; Liu, Peng‐fei
Abstract: The bacterium Aeromonas salmonicida is the pathogen responsible for furunculosis, which is a serious disease of salmonids. This disease has a significant economic impact on the economic benefits of the global salmon farming industry. However, the pathogenesis of this disease in fish is still unknown. Members of the aldehyde dehydrogenase gene (ALDH) superfamily play a key role in the enzyme detoxification of endogenous and exogenous aldehydes. In this study, we obtained a recombinant aldehyde dehydrogenase 7A1 (ALDH7A1) protein to find its functions on Atlantic salmon infected by A. salmonicida . The transcriptional response in the liver of Atlantic salmon ( Salmo salar ) with differing levels of A. salmonicida infection was analysed and compared in order to reveal mechanisms by which ALDH7A1 may confer infection resistance. With the addition of ALDH7A1 protein, it was found that a total of 13, 369 genes were annotated with one or more KEGG and localized to 360 KEGG pathways in the high concentration infection group. The differential expression genes were more enriched in immune signalling pathways such as the Toll‐like receptor signalling pathway, NF‐kappa B signalling pathway and TNF signalling pathway. On the other hand, at low concentrations of infection, KEGG enriched a smaller number of differential expression genes. However, these differential genes were more concentrated in immune signalling pathways such as the PI3K‐Akt signalling pathway, JAK‐STAT signalling pathway and complement and coagulation cascades. In addition, several known immune‐related genes including HSP90α, HSP70, DNA damage‐inducible transcript 4, integrin alpha 5 and microtubule‐associated protein 2 were among the differentially expressed transcripts. These data provide the first insights into the host–ALDH7A1 vaccine interactome. The results of this study contribute to identifying the potential resistance mechanisms of Atlantic salmon to A. salmonicida infection and determining future treatment strategies.